NON-DISCRIMINATION IN TAX TREATY LAW AND WORLD TRADE LAW the impact of formal, substantive ... and subjective approaches. - DZIURDZ, KASPER (KLUWER LAW INTERNATIONAL, 2019)
Non-discrimination is a central obligation under both tax treaty and trade law. However, in seeking to strike a balance between national and international interests, its application differs in the two areas of practice. This book explains the policy issues and how non-discrimination analysis works, provides a comprehensive review of non-discrimination rules in WTO and tax treaty law, combining a critical commentary on case law with proposals for an innovative concept for solving cases of discrimination in tax treaty law. Among the practical issues affecting non-discrimination examined in detail are the following: implications that can be drawn from the concepts of non-discrimination under WTO law and Article 24 of the OECD Model; direct and indirect discrimination and analysis of comparability in WTO law and tax treaty law; the most-favoured-nation (MFN) and national treatment (NT) rules under the GATT and GATS; the meaning of 'likeness' and 'less favourable treatment'; claiming non-discriminatory tax treatment before tax administrations and courts under a tax treaty; justification of measures against harmful tax competition, low taxation and hybrid mismatch arrangements; thin capitalization rules, progressive tax rates, foreign losses, group taxation and relief from juridical and economic double taxation under Article 24 of the OECD Model; and integrating a justification defence into any stage of a non-discrimination analysis. The author establishes to what extent formal, substantive and subjective approaches may be applied in a non-discrimination analysis, providing the reasons for the approaches taken. A two-step comparability procedure is applied to selected cases of potential tax discrimination, demonstrating how policy arguments can be addressed under Article 24 of the OECD Model.